Does Effect of Time Management with Motivation Level and Learning Achievement Students of Vocational High School? - Muzakhi, Agung; Muhammad Aris Ichwanto; Cynthia Permata Dewi; Eko Suwarno; Tee Tze Kiong (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This study aims to determine the relationship between time management so that motivation and learning achievement of vocational students can increase. Methodology: This research uses descriptive analysis The research was held at Malang 6 Vocational High School with a population of class XII DPIB totaling 64 people and samples were taken from the entire population. Data collection using questionnaire distribution. This instrument adopts previous research with validity and reliability values that have fulfilled the criteria. Main Findings: The results of descriptive analysis of time management get an average score of 29.02 or if the percentage is equal to 72.55% and has a meaning in the level of variable development, which is at a fairly high level. The effect of time management has an r square of 4.6%, although the variable is weak against the variables of motivation and learning achievement of vocational students but still has a positive effect. Novelty/Originality of this study: This study is to determine if time management has an effect on increasing the motivation and achievement of vocational students. The impact of this research is as a reference for future researchers to conduct research further. Then this research has an impact on schools and related agencies regarding time management arrangements in schools.